Antifungal-resistant mucorales in different indoor environments - Aranha Caetano, Liliana (2018)
This paper sought to address the prevalence of Mucorales in different indoor environments in Portugal. Environmental samples (183 in total) were collected at dwellings (n = 79) and workplaces (bakeries, swine farms, taxis, waste-sorting plants) (n = 93) by passive sampling using electrostatic dust collector (EDC), air-conditioning filters, litter, and/or raw materials. Samples were inoculated onto non-selective MEA and DG18 media and were screened for antifungal drug-resistance in azole-supplemented agar Sabouraud media. A probe-based Mucorales-specific real-time PCR assay (Muc18S) was used to detect Mucorales in complement to conventional culture-based methods. Mucorales order was found as more prevalent in air-conditioning filters from waste-sorting fork lifters (35.7%). Amongst Mucorales isolates able to grow in azole-supplemented media, 16 isolates of Mucor sp., Rhizopus sp. or Rhizomucor sp. were not susceptible to 1 mg/L voriconazole, and four isolates of Mucor sp. or Rhizopus sp. were not susceptible to 4 mg/L itraconazole. In conclusion, a combination of the culture-based and molecular methods proved to be reliable for Mucorales order identification in complex environmental samples.